THE INFLUENCE OF CAPITAL STRUCTURE, PROFITABILITY AND LIQUIDITY ON THE VALUE OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - William, Glenn; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2024)
This research aims to obtain empirical evidence about the influence of capital structure, profitability and liquidity on the value of non-cyclical consumer goods companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The total sample for this research was 78 non-cyclical consumer goods companies selected using the purposive sampling method. This research data was analyzed using multiple linear regression analysis techniques processed with SPSS (Statistical Product and Service Solutions) software. The results of this research show that capital structure, liquidity and profitability have a significant positive influence on company value.